Transition and Harmonization of the Provisions on Hypotheek and Credietverband regarding the Recognition and Adjustment of the Transitional Provisions of Security Rights - Sunggu, Hengki Ompu; Santoso, Budi; Sulistyarini, Rachmi; Kusuma Dewi, Amelia Sri; Widhiyanti, Hanif Nur (Problems of legality, 2025)
This study explores the legal recognition and transition of property security systems from the Dutch colonial instruments Hypotheek and Credietverband to the national system of Security Rights as regulated under Law No. 4 of 1996 concerning Mortgage Rights. Using a normative juridical approach, the research reveals that legal acknowledgment of the legacy systems is still maintained under Article 57 of the Basic Agrarian Law (UUPA) and Article 24 of the Law on Mortgage Rights (UUHT). However, the absence of a clear and systematic conversion mechanism has created disharmony within the legal system, especially regarding land registration and enforcement practices. This has led to legal uncertainty, particularly in banking and credit sectors where the execution of collateral is essential. The Supreme Court Decision No. 1947 K/Pdt/2010 serves as a case study highlighting the legal ambiguity and operational challenges that arise from this transitional gap. To ensure legal certainty and economic stability, this study recommends legal harmonization through technical regulations, digital archiving of historical security documents, and capacity building for legal institutions and stakeholders.